Researching on SHRM: An analysis of the debate over the role played by human resources in firm success - Fernando Martín Alcázar; Pedro Miguel Romero Fernández; Gonzalo Sánchez Gardey (Management Revue, 2005)
Many different models have been recently proposed to explain the contribution of human resource management to organizational performance, drawing on diverse theoretical frameworks and using many different methodologies. Trying to shed light on the complex state of the art in this field of research, this paper proposes an analysis of the discipline, drawing both on a review of the literature and data obtained from an online questionnaire distributed to human resource management scholars.
Keywords: 650; Strategic Human Resource Management; performance; review of the literature; state of the art; theories; methodologies; Personalmanagement; Strategisches Management; Organisationsforschung; Wissenschaftliche Methode; Theorie